Implications of high throughput sequencing of plant viruses in biosecurity – a decade of progress? - Fox, Adrian; Botermans, Marleen; Ziebell, Heiko; Fowkes, Aimee R.; Fontdevila Pareta, Nuria; Massart, Sebastien; Rodoni, Brendan; Chooi , Kar Mun; Kreuze, Jan; Kumar, P. Lava; Cuellar, Wilmer J.; Carvajal-Yepes, Monica; et al. (Peer Community Journal)

(untitled)
In the 15 years since High Throughput Sequencing (HTS) was first used for the detection and identification of plant viruses, the technology has matured and is now being used in frontline plant biosecurity applications. Anticipating the challenges this new approach was starting to reveal, recommendations were made a decade ago to streamline the application of these technologies. The recommendations were (1) for countries to increase baseline surveillance, (2) to address nomenclature for “data inferred” new viral sequence to differentiate from characterised viruses, and (3) to increase the focus on fundamental biological research to deal with the deluge of new discoveries. Here, we review the progress made on these recommendations in the intervening decade and discuss the anticipated future challenges posed by the broader adoption of HTS in routine biosecurity applications, especially as we move towards a potential asymptote in the rate of virus discovery. The three initial recommendations are still relevant, however, the decade of discovery and development has led to a change in approaches and ways of thinking. A fourth recommendation is made here, to reduce the biosecurity risks through equal inclusion and access to research and technology, locally and globally. This equality will create increased consonance between community members, researchers, risk analysts, biosecurity authorities, and policy makers at national and international levels and a step change reduction of biosecurity incursions of phytopathogenic viruses.